Pemberdayaan kelompok karang taruna dalam kegiatan citizen journalism di Desa Mencirim Kecamatan Kutalimbaru, Kabupaten Deli Serdang - Dedi Sahputra; Effiati Juliana Hasibuan; Rizki Muliono (Riau Journal of Empowerment, 2022)
The problem of drug abuse and criminal acts that occurred in the village of Mecirim, Kutalimbaru District, Deli Serdang Regency, North Sumatra has involved young people. Community service activities are carried out to empower youth groups by increasing creativity through citizen journalism activities, and to maximize the use of digital technology so that the involvement of youth groups in public accountability through the media is maximized so that they are more empowered in social roles in society. The method used is through, first, training through face-to-face lectures by providing citizen journalism material and making personal blogs. Second, face-to-face guidance in the form of editing citizen journalism products produced by youth groups. Third, evaluate the delivery and loading of citizen journalism products to the mass media. The results achieved from this activity are increased knowledge and understanding and skills of youth groups about citizen journalism and citizen journalism activities carried out by youth groups by sending journalistic works published by online mass media.